E-cigarette exposure causes early pro-atherogenic changes in an inducible murine model of atherosclerosis - Alakhtar, Bayan; Guilbert, Cynthia; Subramaniam, Nivetha; Caruana, Vincenza; Makhani, Kiran; Baglole, Carolyn J.; Mann, Koren K. (Frontiers in Toxicology, 2023)
Evidence suggests that e-cigarette use (vaping) increases cardiovascular disease risk, but decades are needed before people who vape would develop pathology. Thus, murine models of atherosclerosis can be utilized as tools to understand disease susceptibility, risk and pathogenesis. Moreover, there is a poor understanding of how risk factors for atherosclerosis (i.e., hyperlipidemia, high-fat diet) intersect with vaping to promote disease risk. Herein, we evaluated whether there was early evidence of atherosclerosis in an inducible hyperlipidemic mouse exposed to aerosol from commercial pod-style devices and e-liquid. Mice were injected with adeno-associated virus containing the human protein convertase subtilisin/kexin type 9 (PCSK9) variant to promote hyperlipidemia. These mice were fed a high-fat diet and exposed to room air or aerosol derived from JUUL pods containing polyethylene glycol/vegetable glycerin (PG/VG) or 5% nicotine with mango flavoring for 4 weeks; this timepoint was utilized to assess markers of atherosclerosis that may occur prior to the development of atherosclerotic plaques.These data show that various parameters including weight, circulating lipoprotein/glucose levels, and splenic immune cells were significantly affected by exposure to PG/VG and/or nicotinecontaining aerosols. Not only can this mouse model be utilized for chronic vaping studies to assess the vascular pathology but these data support that vaping is not risk-free and may increase CVD outcomes later in life.